The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.7150/ijms.42238
|View full text |Cite
|
Sign up to set email alerts
|

The Immune Privilege of the Intervertebral Disc: Implications for Intervertebral Disc Degeneration Treatment

Abstract: The intervertebral disc (IVD) is the largest avascular organ of the body. It is composed of three parts: the nucleus pulposus (NP), the annulus fibrosus (AF) and the cartilaginous endplate (CEP). The central NP is surrounded by the AF and sandwiched by the two CEPs ever since its formation. This unique structure isolates the NP from the immune system of the host. Additionally, molecular factors expressed in IVD have been shown inhibitive effect on immune cells and cytokines infiltration. Therefore, the IVD has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
138
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(156 citation statements)
references
References 87 publications
5
138
0
Order By: Relevance
“…Interestingly, these modules all showed a tendency for convex patterns with upward expression toward the OAF regions, in both lateral and anteroposterior directions, in all levels, combined or separated (Figure 3F-H; Figure 3-figure supplement 3B-D). The higher proportions of ECM, muscle contraction and immune system proteins in the OAF are consistent with the contractile function of the AF (Nakai et al, 2016), and with the NP being avascular and "immune-privileged" in a young homeostatic environment (Sun et al, 2020).…”
Section: Expression Modules Show Lateral and Anteroposterior Trendssupporting
confidence: 62%
“…Interestingly, these modules all showed a tendency for convex patterns with upward expression toward the OAF regions, in both lateral and anteroposterior directions, in all levels, combined or separated (Figure 3F-H; Figure 3-figure supplement 3B-D). The higher proportions of ECM, muscle contraction and immune system proteins in the OAF are consistent with the contractile function of the AF (Nakai et al, 2016), and with the NP being avascular and "immune-privileged" in a young homeostatic environment (Sun et al, 2020).…”
Section: Expression Modules Show Lateral and Anteroposterior Trendssupporting
confidence: 62%
“…Interestingly, these modules all showed a tendency for convex patterns with upward expression toward the OAF regions, in both lateral and anteroposterior directions, in all levels, combined or separated ( Figure 3F-H; Supplemental S8B-D). The higher proportions of ECM, muscle contraction and immune system proteins in the OAF are consistent with the contractile function of the AF (Nakai et al, 2016), and with the NP being avascular and "immune-privileged" in a young homeostatic environment (Sun et al, 2020).…”
Section: Expression Modules Show Lateral and Anteroposterior Trendssupporting
confidence: 62%
“…However, the disappearance of notochordal cells in human IVD is a matter of debate, since a considerable proportion of cells within NP of adults display notochord-like phenotype [ 15 ]. Animal studies found that both NP cells and notochordal cells originate from the embryonic notochord [ 14 ].…”
Section: On Intervertebral Discmentioning
confidence: 99%